1993
DOI: 10.2220/biomedres.14.99
|View full text |Cite
|
Sign up to set email alerts
|

<b>INHIBITION OF DNA SYNTHESIS BY EDTA AND ITS CANCELLATION BY ZINC IN PRIMARY CULTURES OF ADULT RAT </b><b>HEPATOCYTES </b>

Abstract: Adult rat hepatocytes actively proliferate in a serum-free primary culture. Addition of 0.5 mM ethylenediamine tetraacetic acid (EDTA) to the culture medium inhibited DNA synthesis completely, while ethyleneglycol bis(,8-aminoethyl ether)-M N'--tetraacetic acid (EGTA) had no effect on DNA synthesis. The inhibition of DNA synthesis by EDTA was completely cancelled by simultaneous addition of Zn". Other divalent metals examined (Ca2+, Mg", Fe", Cu", and Mn") were ineffective. The rate of the DNA synthesis was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…This finding indicates that zinc is needed at the G1/S transition of the cell cycle for DNA synthesis. A similar phenomenon was observed when ethylenediaminetetraacetic acid (EDTA) was added to primary cultures of adult rat hepatocytes [6]. Zinc is also required for a process contemporaneous with the S phase and for subsequent transition of the cells through G2/M [7].…”
Section: Introductionsupporting
confidence: 52%
“…This finding indicates that zinc is needed at the G1/S transition of the cell cycle for DNA synthesis. A similar phenomenon was observed when ethylenediaminetetraacetic acid (EDTA) was added to primary cultures of adult rat hepatocytes [6]. Zinc is also required for a process contemporaneous with the S phase and for subsequent transition of the cells through G2/M [7].…”
Section: Introductionsupporting
confidence: 52%
“…Yet, contradictory findings regarding the relationship between the appearance of MT in hepatocyte culture and DNA synthesis have also been reported. 16 Although some studies have demonstrated MT induction by different growth factors in cell MT gene expression as influenced by growth factors has not been studied extensively in rat hepatocytes. The current work was therefore undertaken to investigate MT expression in hepatocytes under growth stimuli.…”
mentioning
confidence: 99%
“…Thus, the ratio of cytosolic/nuclear fluorescence 7 can be used as a readout for CDK2 activity and serves a 'molecular timer' for progression 8 through the cell cycle. As described previously, CDK2 activity defines subpopulations of cells 9 with different cell fates in a population of naturally cycling cells (16,17,19,42,43). When the 10 CDK2 ratio remains low after mitosis (CDK2 low ), a cell is classified as quiescent whereas when 11 CDK2 activity increases above a defined threshold within 4 hrs after mitosis (CDK2 inc ), a cell is 12 born committed to cell cycle entry ( Figure 2A).…”
Section: Mild Zn 2+ Deficiency Induces Cellular Quiescence and Stallimentioning
confidence: 76%
“…Analysis of mitosis events revealed that these cells did not 7 divide before entering the CDK2 low state. These results suggest a significant increase in the 8 number of cells that go quiescent after mitosis and the emergence of a new cell fate, where cells 9 attempt to re-enter the cell cycle but stall part-way through under conditions of Zn 2+ deficiency. 10 To further define how Zn 2+ deficiency influences cell fate and characterize the 11 consequences of the altered CDK2 activity profile in ZD cells, we examined a downstream 12 CDK2 substrate, retinoblastoma protein (Rb).…”
Section: Mild Zn 2+ Deficiency Induces Cellular Quiescence and Stallimentioning
confidence: 87%
See 1 more Smart Citation